Alignment of systematic reviews published in the Cochrane Database of Systematic Reviews and the Database of Abstracts and Reviews of Effectiveness with global burden-of-disease data: a bibliographic analysis. Issue 7 (17th April 2015) - Yoong, Sze Lin; Hall, Alix; Williams, Christopher M; Skelton, Eliza; Oldmeadow, Christopher; Wiggers, John; Karimkhani, Chante; Boyers, Lindsay N; Dellavalle, Robert P; Hilton, John; Wolfenden, Luke
Abstract : Background: Systematic reviews of high-quality evidence are used to inform policy and practice. To improve community health, the production of such reviews should align with burden of disease. This study aims to assess if the volume of research output from systematic reviews proportionally aligns with burden of disease assessed using percentages of mortality and disability-adjusted life years (DALYs). Methods: A cross-sectional audit of reviews published between January 2012 and August 2013 in the Cochrane Database of Systematic Reviews (CDSR) and Database of Abstracts of Reviews of Effects (DARE) was undertaken. Percentages of mortality and DALYs were obtained from the 2010 Global Burden of Disease study. Standardised residual differences (SRD) based on percentages of mortality and DALYs were calculated, where conditions with SRD of more than or less than three were considered overstudied or understudied, respectively. Results: 1029 reviews from CDSR and 1928 reviews from DARE were examined. There was a significant correlation between percentage DALYs and systematic reviews published in CDSR and DARE databases (CDSR: r=0.68, p=0.001; DARE: r=0.60, p<0.001). There was no significant correlation between percentage mortality and number of systematic reviews published in either database (CDSR: r=0.34, p=0.14; DARE: r=0.22, p=0.34). Relative to percentage of mortality, mental and behavioural disorders, musculoskeletal conditions and other non-communicable diseases were overstudied. Maternal disorders were overstudied relative to percentages of mortality and DALYs in CDSR. Conclusions: The focus of systematic reviews is moderately correlated with DALYs. A number of conditions may be overstudied relative to percentage of mortality particularly in the context of health and medical reviews.